Penentuan Lokasi Alternatif Tempat Pembuangan Akhir Sampah Di Kecamatan Bathin Solapan Kabupaten Bengkalis - Uliwati, Elisa; Lubis, Satia Negara; Thoha, Achmad Siddik (Jurnal Serambi Engineering, 2025)
The increase in waste generation and the lack of waste management efforts in landfills (TPA) continuously causes the capacity of the landfill to be full. Determination of the location of a new landfill designation is one solution to avoid environmental pollution problems. The purpose of this study is to determine the location of the waste landfill feasible zone based on regional criteria and determine the location of alternative waste landfill designations based on the exclusion criteria in Bathin Solapan District. This research uses primary data and secondary data. The research method used is descriptive research with a quantitative approach. In this research, the location of waste landfill is determined by adjusting SNI 19-3241-1994 and analyzed by overlay analysis and scoring. The samples in this study were several locations determined from the results of overlaying several land unit maps. Sampling was done by purposive sampling. The results showed that there was a waste landfill feasibility zone in Bathin Solapan District covering an area of 21,831.1 Ha spread across 13 villages. The alternative location of the waste landfill designation based on the elimination criteria is located in Petani Village, Jalan Rangau km 17 with a land area of 9.16 Ha and a suitability value of 664. Based on the opt-out stage analysis, the selected alternative site has a more positive socio-economic impact compared to the other sites.